Telemedicine Intervention to Improve Long-Term Risk Factor Control and Body Composition in Persons with High Cardiovascular Risk: Results from a Randomized Trial - Nana Pogosova; Yulia Yufereva; Olga Sokolova; Anara Yusubova; Alexander Suvorov; Hugo Saner (Ubiquity Press, 2021)
Telehealth strategies may offer an advantage over standard institutional based interventions for improvement of cardiovascular risk in high-risk patients long-term   Background: Telehealth strategies are increasingly used to support people at high cardiovascular risk long-term, but is it unclear if these interventions are effective at improving cardiovascular risk. Objective: To evaluate the effects of a telemedicine technology-based program on risk factor control and body composition in patients at high cardiovascular risk. Methods: This is a population based randomized controlled trial. 100 patients at high and very high cardiovascular risk were randomly assigned to a telemedicine technology-based program consisting of: Comprehensive counseling on risk factors delivered by a physician; biweekly remote support via phone delivered by a trained nurse during the first three months after enrollment; and a control group receiving routine care with individual single-session counseling on patients' current risk factors without further support. The follow-up period was 1 year. Results: Mean age of participants was 59.9 ± 4.5 years, 80% were women. Weight (-0.582; p < 0.001), waist circumference (-0.429; p = 0.01), body mass index (-0.216; p < 0.001) diastolic blood pressure (-0.881; p = 0.04), total cholesterol (-0.149; p = 0.01) and LDL cholesterol (-0.123; p = 0.003) were lower in the intervention group compared to the control group after 12-month. Body fat mass was also lower (-0.352; p = 0.01) and lean mass was higher (0.92; p = 0.03) in the intervention group. Anxiety scores (-2.5; p < 0.002) and depression scores (-2.6; p < 0.001) were also lower in the intervention group. Conclusions: Among older people at high cardiovascular risk, the addition of telehealth strategies using remote support by phone calls over a period of 3 month resulted in small but significant improvements of cardiovascular risk factors, body composition, anxiety, and depression which are maintained long-term. Such telehealth strategies may offer an advantage over standard institution-based interventions.